Adoptive T cell therapy for solid tumors: current landscape and future challenges - Víctor Albarrán; María San Román; Javier Pozas; Jesús Chamorro; Diana Isabel Rosero; Patricia Guerrero; Juan Carlos Calvo; Carlos González; Coral García de Quevedo; Patricia Pérez de Aguado; Jaime Moreno; Alfonso Cortés; et al. (Frontiers in Immunology, 2024)
Adoptive cell therapy (ACT) comprises different strategies to enhance the activity of T lymphocytes and other effector cells that orchestrate the antitumor immune response, including chimeric antigen receptor (CAR) T-cell therapy, T-cell receptor (TCR) gene-modified T cells, and therapy with tumor-infiltrating lymphocytes (TILs). The outstanding results of CAR-T cells in some hematologic malignancies have launched the investigation of ACT in patients with refractory solid malignancies. However, certain characteristics of solid tumors, such as their antigenic heterogeneity and immunosuppressive microenvironment, hamper the efficacy of antigen-targeted treatments. Other ACT modalities, such as TIL therapy, have emerged as promising new strategies. TIL therapy has shown safety and promising activity in certain immunogenic cancers, mainly advanced melanoma, with an exciting rationale for its combination with immune checkpoint inhibitors. However, the implementation of TIL therapy in clinical practice is hindered by several biological, logistic, and economic challenges. In this review, we aim to summarize the current knowledge, available clinical results, and potential areas of future research regarding the use of T cell therapy in patients with solid tumors